Students’ Epistemic Game according to SOLO Taxonomy in Completing Fluid Mechanics Problem - M. Dewi Manikta Puspitasari; Kuni Nadliroh; Muhammad Najibulloh Muzaki (Jurnal Pembelajaran Fisika, 2020)
The purpose of this study is to describe the students’ epistemic game of high physics-capable. This study is qualitative. The participants are students taking fluid mechanics courses. The collect data of this study use fluid mechanics test, physics understanding test, and interview. The understanding test determines the students’ understanding level, while the determining students’ epistemic game by SOLO taxonomy uses the fluid mechanic's test. The students complete the first test by using mapping mathematics to meaning at a relational level and transliteration to mathematics at a multi structural level. Pictorial analysis in level extended abstract and transliteration to mathematics in level relational are used by the students in completing the problem of the second test. Meanwhile, this study result showed that mapping mathematics to the meaning and recursive plug and chug at a relational level is used by the students for completing the third test. Furthermore, the students completing the fourth test used transliteration to mathematics and recursive plug and chug at a relational level The students’ epistemic game by SOLO taxonomy of this study can be used to develop physics learning.Keywords: epistemic game, SOLO taxonomy, fluid mechanicsDOI: http://dx.doi.org/10.23960/jpf.v8.n2.202005